Sea witch - Henning, Sarah (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
Ever since her best friend, Anna, drowned, Evie has been an outcast in her small fishing town. Hiding her talents, mourning her loss, drowning in her guilt. Then a girl with an uncanny resemblance to Anna appears offshore and, though the girl denies it, Evie is convinced that her best friend actually survived. That her own magic wasn't so powerless after all ... The rise of Hans Christian Andersen's iconic villainess is a heart-wrenching story of friendship, betrayal, and a girl pushed beyond her limits-- to become a monster.--From dust jacket.